Solution‐Processed Tandem Quantum‐Dot Light‐Emitting Diodes with Dual Charge Generation Interfaces: Achieving Over Threefold Efficiency Enhancement - Shu‐Guang Meng; Wan‐Shan Shen; Wei‐Zhi Liu; Sheng‐Nan Li; Dong‐Ying Zhou; Liang‐Sheng Liao (Advanced Materials Interfaces, 2024)
Abstract Despite the commercialization of thermally evaporated tandem organic light‐emitting diodes (OLEDs), challenges remain for solution‐processed tandem quantum‐dot light‐emitting diodes (QLEDs), including low efficiency and solvent‐induced damage to functional layers. Therefore, there is an urgent need for the optimization of the interconnecting layer (ICL) design in order to fabricate high‐performance solution‐processed tandem QLEDs. Here, by introducing a phosphomolybdic acid (PMA) layer between poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) and poly(9‐vinylcarbazole) (PVK), an novel ICL, PVK/PMA/PEDOT:PSS/ZnO is proposed, with dual charge generation interfaces (CGIs): PVK/PMA and PEDOT:PSS/ZnO. The PMA interlayer serves not only smoothing the morphology of PEDOT:PSS to improve charge transport, but also forming a PVK/PMA CGI to enhance charge generation. Based on the excellent electrical and optical properties of the dual‐CGI ICL, the solution‐processed inverted tandem red QLEDs achieve an increased external quantum efficiency (EQE) of over three times compared to single‐junction devices. This provides a novel approach for the high‐efficiency solution‐processed tandem QLEDs, paving the way for the practical application of QLEDs.